CONTEMPORARY ISLAMIC THOUGHT: Answering the Challenges of Da'wah in the Digital Era - Azmi, Aulia Ulul; Rifai, Achmad (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2025)
This research discusses contemporary Islamic thought in facing the challenges of da'wah in the digital era, which is characterized by the rapid development of technology and changes in people's communication patterns. The main objective of this study is to identify and analyze new approaches in da'wah that are in accordance with the digital context, as well as to reveal the thoughts of contemporary Muslim scholars on da'wah strategies that are effective and relevant to modern society. The research method used is qualitative with a descriptive-analytical approach. Primary data was obtained through in-depth interviews with digital da'wah figures, Muslim scholars, and media practitioners, while secondary data was collected from literature in the form of books, journals, articles, and content analysis from da'wah digital media. Data analysis was carried out with the Miles and Huberman interactive analysis model, which included data reduction, data presentation, and conclusion drawn. The results of the study show that contemporary Islamic thought in answering the challenges of da'wah in the digital era has a common problem. First, the relevance and contextualization of Islamic teachings. Second, the use of digital media for effective da'wah, third, facing the challenges of spreading hoaxes and radicalism, fourth, the importance of moderate and inclusive da'wah, fifth, emphasizing digital literacy and ethics in da'wah, and sixth, the role of scholars and scholars in the development of digital da'wah. The implications ofthis study confirm that contemporary Islamic thought must be adaptive to the challenges of the digital era, utilizing technology for da'wah that is moderate, inclusive, and relevant to the needs of modern society.